STUDI KEMAMPUAN VERTICAL SUBSURFACE FLOW CONSTRUCTED WETLANDS DALAM MENYISIHKAN COD, NITRIT, DAN NITRAT PADA AIR LINDI (STUDI KASUS: TPA NGRONGGO, SALATIGA) - Ismaryanto Gunawan; Wiharyanto Oktiawan; Mochtar Hadiwidodo (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTLeachate is one of resulting negative impact from landfilling in Indonesia. In common leachate containing an organic and inorganic matter with high concentration. Therefore, treatment of the leachate is essential before it could be discharged directly into the receiving water bodies. One of technology to treat landfill leachate which is by use of biological treatment. But this processing apparently is still result organic and inorganic content one high enough. Therefore, necessary continuing processing alternative which is by use of system Constructed Wetlands. This research intent to know decrease of concentration COD, nitrit and nitrate, and removal efficiency on system Vertical Subsurface Flow Constructed Wetlands by use of plant Scirpus grossus. Besides that, the impact of variation amount plants and residence time would be analized. The laboratory research was conducted with use 4 reactors. Reactor A with 4 plants, reactor B with 6 plants, reactor C with 8 plants, and rector C without plant. Four of the reactors operated at a flow rate of 10,5 ml / minutes for residence time 3 days, 5,3 ml / minutes for residence time 6 days, and 3,5 ml / minutes for residence time 9 days. System Vertical Subsurface Flow Constructed Wetlands by use of plant Scirpus grossus (lingi) can removal concentration of COD, nitrit, and nitrate. The highest removal efficiency for COD, nitrit and nitrat were 63,4%, 57,6%, and 59,0% respectively. All of them was reached by reactor C with residence time 9 days. Besides that, decrease concentrations COD, nitrit and nitrate on system Vertical Subsurface Flow Constructed Wetlands regarded by amount plants and residence time.